2012
DOI: 10.1038/ki.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age affects the outcome-predictive power of RIFLE classification in geriatric patients with acute kidney injury

Abstract: The RIFLE (risk, injury, failure, loss, and end-stage) classification is widely used to gauge the severity of acute kidney injury, but its efficacy has not been formally tested in geriatric patients. To correct this we conducted a prospective observational study in a multicenter cohort of 3931 elderly patients (65 years of age or older) who developed acute kidney injury in accordance with the RIFLE creatinine criteria after major surgery. We studied the predictive power of the RIFLE classification for in-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 40 publications
6
48
2
Order By: Relevance
“…[3][4][5]8,9,12 We found that 27% of geriatric patients had AKI and most of them had AKI stage 1, in agreement with the literature. 15,16 The in-ICU mortality of geriatric AKI patients (48.1%) was higher than the other studies (16%-40%). [3][4][5]16 However, these studies also included elderly patients not only in ICUs but also in general wards of the hospital.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…[3][4][5]8,9,12 We found that 27% of geriatric patients had AKI and most of them had AKI stage 1, in agreement with the literature. 15,16 The in-ICU mortality of geriatric AKI patients (48.1%) was higher than the other studies (16%-40%). [3][4][5]16 However, these studies also included elderly patients not only in ICUs but also in general wards of the hospital.…”
Section: Discussioncontrasting
confidence: 44%
“…This is due to many reasons, including elderly are more likely to have renal structural decline and multiple comorbidities. 3,8,9,12,14,15 Previous studies reported the incidence of AKI among geriatric patients ranged from 22% to 40%, with most patients having stage 1 disease. [3][4][5]8,9,12 We found that 27% of geriatric patients had AKI and most of them had AKI stage 1, in agreement with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another sensitivity analysis excluding these patients resulted essentially similar (detailed in result section). Finally, AKI severity could not be adjusted owing to the absence of urine output data in our database, so AKI was coded as present or not (15,16,35). As the current study is the retrospective analysis of our postoperative patients' registry, applications beyond ethnicity/age-matched cohorts could be questionable.…”
Section: Limitationsmentioning
confidence: 97%
“…Renal Failure) database (15). Participating centers consist of National Taiwan University Hospital and its regional branch hospitals.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…13,22 AKI has been well described in geriatric population, and an increased incidence of AKI becomes higher than previous studies (2-25%). 24 The proportion of AKI in these patients is 33.6% due to the use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) prior to surgical intervention. The association between preoperative management of ACEIs and/or ARBs and cardiovascular surgery should increase the incidence of AKI $27.2%.…”
Section: Discussionmentioning
confidence: 99%